2007
DOI: 10.1002/pi.2343
|View full text |Cite
|
Sign up to set email alerts
|

Polyamide–silica nanocomposites: mechanical, morphological and thermomechanical investigations

Abstract: BACKGROUND: The physical properties of polyamides can be enhanced through incorporation of inorganic micro-and nanofillers such as silica nanoparticles. Transparent sol-gel-derived organic-inorganic nanocomposites were successfully prepared by in situ incorporation of a silica network into poly(trimethylhexamethylene terephthalamide) using diethylamine as catalyst. Thin films containing various proportions of inorganic network obtained by evaporating the solvent were characterized using mechanical, dynamic mec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
51
0
1

Year Published

2009
2009
2016
2016

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 78 publications
(56 citation statements)
references
References 32 publications
4
51
0
1
Order By: Relevance
“…Recently, it has been shown that physical properties of polyamides can be improved by the addition of both inorganic micro -and nanofi llers to a poly(trimethylhexamethylene terephthalamide) matrix [2] . For this, the composite samples were prepared using a sol -gel technique, with the incorporation in situ of a silica precursor ( tetraethyl orthosilicate ; TEOS ), using diethylamine as the catalyst.…”
Section: Nanoclays and Their Infl Uence On The Thermomechanical Propementioning
confidence: 99%
See 1 more Smart Citation
“…Recently, it has been shown that physical properties of polyamides can be improved by the addition of both inorganic micro -and nanofi llers to a poly(trimethylhexamethylene terephthalamide) matrix [2] . For this, the composite samples were prepared using a sol -gel technique, with the incorporation in situ of a silica precursor ( tetraethyl orthosilicate ; TEOS ), using diethylamine as the catalyst.…”
Section: Nanoclays and Their Infl Uence On The Thermomechanical Propementioning
confidence: 99%
“…Yet, by using knowledge acquired with " old " composite materials, a great deal of success has been achieved in preparing nanocomposites with good miscibility and compatibility so as to guarantee the desired properties, based largely on the chemical modifi cation of the silicates that are used to introduce an organic character to a hydrophilic ceramic. To date, many reports have been produced on organic -inorganic composites that combine the desirable properties of a ceramic phase (heat resistance, retention of mechanical properties at elevated temperatures, low thermal expansion) with those of organic polymers (toughness, ductility, processability); the result has been the development of novel properties that are not demonstrated by regular composites [2] .…”
Section: Introductionmentioning
confidence: 99%
“…Aromatic polyamides are noted for high transparency, excellent mechanical properties, heat resistance, good char yield, low flammability, good barrier properties, and outstanding strengthto-weight ratios and solvent resistance [1][2][3][4]; however, they are difficult to process because of limited solubility and high glass transition (T g ) [5][6][7]. The processing of these polymers has been greatly hindered because they lack softening or melting property at usual processing temperature, and they tend to decompose at the softening temperature.…”
Section: Introductionmentioning
confidence: 99%
“…[14] Among the various polymers used for hybrid composites, polyamides have been particularly popular because they offer excellent physical and chemical properties, thermal and oxidative stability, flame resistance, and superior mechanical and dielectric properties. [15][16][17] However, they are difficult to process because of limited solubility and high glass transition (T g ). [15,18] The processing of these polymers has been greatly hindered because they lack softening or melting property at usual processing temperature, and they tend to decompose at the softening temperature.…”
Section: Introductionmentioning
confidence: 99%
“…[15][16][17] However, they are difficult to process because of limited solubility and high glass transition (T g ). [15,18] The processing of these polymers has been greatly hindered because they lack softening or melting property at usual processing temperature, and they tend to decompose at the softening temperature. Many efforts have been made to create structurally modified aromatic polymers having increased solubility and processability with retention of their high thermal stability.…”
Section: Introductionmentioning
confidence: 99%